Why work beyond 65? Discourse on the Decision to Continue Working or Retire Early - Nilsson, Kerstin (Nordic Journal of Working Life Studies, 2012)
This study examined retirement decisions among people who had left working life before 65 years of age and those working beyond 65 years in an extended working life. The results were used to make a model about their considerations, weighting and decision making, and important factors and themes in working beyond 65 years of age or retiring before 65. The interviewees seemed to have considered and weighed their own best life balance to finally result in their identity as (older) worker or early retiree. They included their work situation and social surroundings in descriptions of their planning and retirement decision making. The most important themes in these descriptions were (i) personal health and well-being; (ii) personal finances; (iii) possibilities for social inclusion; and (iv) possibilities for self-crediting by meaningful activities. Those identifying themselves as older workers had possibilities in their life situation to manage their work in relation to their functional ageing and health situation; felt important to others and socially included in the workplace; and did meaningful tasks and felt empowered in their working life. Those who had left the working life before 65 years of age describe a better possibility to this outside the working life and left as soon as they acquire a sufficient pension. The results and model presented here on how people perceive their identity as older worker or early retiree will hopefully contribute to understanding retirement planning and to the formulation of strategies to extend working life.